Statistical Analysis of the Holdings, Circulation and Acquisitions of the Buley Library Book Collection. - Kobus, Julia (1988)
Keywords: dept.lib; faculty_collection; sabbatical_report

Buley Library Connecticut Room Collection; Holdings List - Hilton C Buley Library; Clarie, Tom; Bennett, Claire (Southern Connecticut State University. Hilton C. Buley Library. Reference Department, 1986)
Publication Title: Buley Library Connecticut Room Collection; holdings list
Keywords: Bibliography; Catalogs; Library catalogs; Connecticut; dept.lib; faculty_collection

Occult/Paranormal Bibliography: An Annotated List of Books Published in English, 1976 Through 1981 - Clarie, Thomas C. (Scarecrow Press, 1984)
English-language books published or reissued between 1976-1981. Arranged alphabetically by authors. Asterisks indicate excellence. Author, title, and subject indexes.
Keywords: Bibliography; Bibliography; Parapsychology; Occultism; dept.lib; faculty_collection

New Haven in 1884 - Shumway, Floyd M.; Hegel, Richard (New Haven Colony Historical Society, 1984)
Keywords: History; New Haven (Conn.); dept.lib; faculty_collection

New Haven: An Illustrated History - Shumway, Floyd M.; Hegel, Richard; New Haven Colony Historical Society (Windsor Publications, 1981)
Keywords: Description and travel; History; New Haven (Conn.); New Haven (Conn.); dept.lib; faculty_collection